2018
DOI: 10.1111/1753-0407.12824
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial appendage occlusion for stroke prevention in diabetes mellitus patients with atrial fibrillation: Long‐term results

Abstract: The present study indicates that LAAO in AF patients with DM has similar safety endpoints and long-term efficacy as LAAO in patients without DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 42 publications
2
24
1
Order By: Relevance
“…Two randomized studies, PROTECT AF [8] and PROTECT AF CAP Registry [24], showed that LAAC is as effective in preventing stroke in patients with nonvalvular AF as warfarin treatment. Authors in previous studies also confirm that LAAC is safe and effective in AF patients [6,7,25] even in patients with higher thromboembolic risk such as those with diabetes [11] or increased age [12].…”
Section: Discussionmentioning
confidence: 74%
“…Two randomized studies, PROTECT AF [8] and PROTECT AF CAP Registry [24], showed that LAAC is as effective in preventing stroke in patients with nonvalvular AF as warfarin treatment. Authors in previous studies also confirm that LAAC is safe and effective in AF patients [6,7,25] even in patients with higher thromboembolic risk such as those with diabetes [11] or increased age [12].…”
Section: Discussionmentioning
confidence: 74%
“…Our procedure was performed via thoracoscopic access and therefore was less traumatic for the patient. Moreover, the use of an epicardial approach enables simultaneous performance of left atrial appendage occlusion with the LARIAT system to decrease the risk of stroke [6,7]. In the study by Coolbear et al [8] only 13% of patients were free of AF after nearly four years of observation following surgical RF ablation.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, our analysis was limited to endoluminal LAAO devices. Epicardial systems, such as the LARIAT system (SentreHEART Inc., Redwood City, CA, USA) were excluded from the study as the provided analyses were not applicable to epicardial systems …”
Section: Discussionmentioning
confidence: 99%
“…Epicardial systems, such as the LARIAT system (SentreHEART Inc., Redwood City, CA, USA) were excluded from the study as the provided analyses were not applicable to epicardial systems. 17,18 Although the study is subject to several limitations, it is a unique data set comparing different LAAO devices under largely standardized conditions and aims to increase the understanding of the mechanical behavior of these devices.…”
Section: Limitationsmentioning
confidence: 99%